2021
DOI: 10.1186/s40594-021-00306-y
|View full text |Cite
|
Sign up to set email alerts
|

Am I getting through? Surveying students on what messages they recall from the first day of STEM classes

Abstract: Background The first day of class helps students learn about what to expect from their instructors and courses. Messaging used by instructors, which varies in content and approach on the first day, shapes classroom social dynamics and can affect subsequent learning in a course. Prior work established the non-content Instructor Talk Framework to describe the language that instructors use to create learning environments, but little is known about the extent to which students detect those messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…While previous research has found that many instructors provide this type of guidance on the first day of class ( Lane et al. , 2021 ; Meaders et al. , 2021 ), we have also noticed that students seem to most readily recall this messaging when it has been reiterated consistently across the semester ( Brazeal et al.…”
Section: Discussionmentioning
confidence: 57%
“…While previous research has found that many instructors provide this type of guidance on the first day of class ( Lane et al. , 2021 ; Meaders et al. , 2021 ), we have also noticed that students seem to most readily recall this messaging when it has been reiterated consistently across the semester ( Brazeal et al.…”
Section: Discussionmentioning
confidence: 57%
“…To decrease student anxiety while describing laboratory expectations, instructors can discuss the laboratory curriculum and environment, including the roles the instructor and teaching assistants have in providing support in the course. 25 The results of this research also provide guidance for college chemistry instructors to support students' time management and study skills. There are a variety of options instructors can such as creating weekly planners distributed through a Learning Management Systems (LMS) as either standalone documents or videos.…”
Section: ■ Discussion and Implicationsmentioning
confidence: 83%
“…1,2,24 These impacts, the unfinished learning, and disrupted and disparate learning experiences are carried into chemistry classrooms by incoming students. Synthesizing these findings with the research on communication during the first day of class 25 suggests that it is beneficial to acknowledge students' pandemic related experiences. This action conveys an understanding of their situation and can emphasize the availability of academic and well-being resources to support students.…”
Section: ■ Discussion and Implicationsmentioning
confidence: 84%
See 2 more Smart Citations